Analysis of Walhi's Advocacy Strategy in Green Open Space Policy in Bandar Lampung City - Himawan Indrajat; Fani Destia; Denden Kurnia Drajat; Bendi Juantara (Iapa Proceedings Conference, 2022)
The development process in Indonesia has currently experienced a very rapid development, especially in the industrial and property sectors. However, this is obviously inversely proportional to environmental management in Indonesia, which basically the development carried out must pay attention to various aspects, one of which is the environmental aspect. Massive development often overrides the ecological or environmental balance in urban areas, including forgetting the importance of abandoning green areas or Green Open Space (RTH). According to the Bandar Lampung City RTRW Evaluation Document, the current RTH area of Bandar Lampung City is 1,895.89 hectares or only 9.61% of the area of Bandar Lampung City. In order to meet the minimum standards for the provision of urban public RTH, Bandar Lampung City must at least strive for the provision of 10.39% or around 2,049 hectares of public RTH. There are seven sub-districts in Bandar Lampung City that are the locations for public RTH distribution, namely Sukarame, Kemiling, Way Halim, Enggal, Tanjung Karang Barat, Bumi Waras and Panjang districts. This study examines the role and contribution made by WALHI Non-Governmental Organizations (NGOs) to the condition of Green Open Space (RTH) in Bandar Lampung City, and aims to provide an analysis of the role and contribution of civil society in its efforts to advocate for RTH policies in Bandar Lampung City and Map the obstacles faced by civil society in advocating for RTH policies in Bandar Lampung City.